Optimized extraction of bioactive compounds from Herba Artemisiae Scopariae with ionic liquids and deep eutectic solvents. Issue 9 (28th May 2017) - Ma, Wanwan; Row, Kyung Ho
ABSTRACT: Ionic liquids with length of alkyl chain and different anions, deep eutectic solvents with choline chloride and 7 different hydrogen bond donors were applied as extraction additives after optimizing the extraction conditions to increase the extraction amounts of rutin, quercetin, and scoparone from Herba Artemisiae Scopariae . The extraction conditions were optimized as follows: refluxing with methanol with a solid/liquid ratio of 1:120 under 60°C for 60 min after changing the different extraction conditions of: extraction methods (dipping, ultrasonic, reflux and soxlet), extraction solvents (methanol, water and ethanol), extraction temperature (30, 40, 50, 60, 70 and 80°C), extraction time (30, 60, 80, 100 and 120 min), extraction ratio of solid to liquid (1:5, 1:10, 1:20, 1:50, 1:100, 1:120 and 1:150). Under these optimal conditions, the best preformed extraction additive among the 7 kinds of ionic liquids and 7 kinds of deep eutectic solvents extraction additives were selected and optimized with its contraction of 0.5mg/mL. Using the most effective extraction additive, [BMIM][Br], 10275.92 µg/g rutin, 899.73 µg/g quercetin, and 554.32 µg/g scoparone were obtained. Overall, ionic liquids and deep eutectic solvents have potential applications as extraction additives for the extraction of bioactive compounds from nature plants. GRAPHICAL ABSTRACT: